Mild synthesis of monodisperse tin nanocrystals and tin chalcogenide hollow nanostructures. Issue 80 (14th September 2017) - Zhao, Xixia; Di, Qian; Wu, Xiaotong; Liu, Yubin; Yu, Yikang; Wei, Guijuan; Zhang, Jun; Quan, Zewei
Abstract : A mild but robust synthetic strategy was developed to synthesize monodisperse Sn nanocrystals with tunable size by using tungsten hexacarbonyl as the reducing agent, and novel tin chalcogenide nanostructures have also been prepared using Sn nanocrystals as templates. Abstract : We report a mild synthetic method to access Sn nanocrystals with tunable diameter and narrow size distribution (6–8%). The self-templated formation of various types of Sn chalcogenide hollow nanostructures including oxides, sulfides, selenides, and tellurides is also demonstrated for the first time. The use of air-stable tungsten hexacarbonyl that produces carbon monoxide at elevated temperature to reduce the SnCl2 precursor and coordinate the nanoparticle surface is thought to play an essential role in this method. This synthesis method is likely to be extended to other metal systems and could find potential applications including battery anodes and catalysts.